The analysis of the sensitivity of vaccination parameters in a tuberculosis transmission model - Chasanah, Siti Laelatul; Ferdias, Pandri; Nurvazly, D E (Universitas Islam Negeri Raden Intan Lampung, 2021)
Tuberculosis (TB) is one of the most dangerous infectious diseases that caused 1,5 million people died from TB in 2018 (including 251.000 people with HIV). As the preventive strategy for the spread of TB, we can use BCG vaccination. This study aims to investigate and analyze the sensitivity of vaccination parameters (to newborns and adults). This model divided the human population into five classes: susceptible , vaccinated , high-risk and low-risk latent, and infectious . Analysis of the mathematical model was discussed by finding the existence and analyzing the model equilibrium's stability based on the Basic Reproduction Number ( ). Furthermore, we determined the sensitivity analysis of the proportion of vaccine and other parameters that affect the TB transmission model. The numerical experiment shows that vaccination to adults more effective than newborns.